Validation of an immunohistochemistry assay to detect turkey coronavirus: A rapid and simple screening tool for limited resource settings - Cardoso, T. C. [UNESP]; Castanheira, T. L. L. [UNESP]; Teixeira, M. C. B. [UNESP]; Rosa, A. C. G. [UNESP]; Hirata, K. Y. [UNESP]; Astolphi, R. D. [UNESP]; Luvizotto, Maria Cecília Rui [UNESP] (Poultry Science Assoc Inc, 2008)
The objective of the present study was to develop and apply the direct immunohistochemistry (D-IHC) assay to search for turkey coronavirus (TCoV) antigens in formalin-fixed embedded-paraffin tissues by the use of biotin-labeled polyclonal antibody. Twenty-eight-day-old embryonated turkey eggs (n = 50) were inoculated with TCoV-purified virus, and 3 d after inoculation, sections from ileum, ileum-cecal junction, and ceca were harvested, fixed in neutral formalin, and embedded in paraffin blocks and used as positive control. In addition, a total of 100 field samples from ileum, ileum-cecal junction, and ceca, collected from 30 to 45-d-old turkeys poults experiencing an outbreak of acute enteritis, were used to search for TCoV by the same D-IHC. All results were compared with those obtained by conventional RT-PCR and indirect fluorescent antibody assay (IFA) for all tested samples. Turkey coronavirus was detected in experimentally infected embryo tissues and also in field samples in 100% of ileum-cecal junction and ceca by the 3 detection procedures. With IFA as a reference assay, sensitivity and specificity of D-IHC were 98 and 58%, whereas sensitivity and specificity of reverse transcription-PCR were 96 and 66%, calculated from the total of tested samples from experimental infection. Each of the examined procedures was highly specific (D-IHC, 93%; RT-PCR, 90%), sensitive (D-IHC, 85%; RT-PCR, 86%), and agreement of both D-IHC and RT-PCR was 99 and 100%, respectively, compared with IFA results obtained from all the field samples. These findings demonstrated the utility of D-IHC for direct detection of TCoV from field samples and considering the sensitivity and specificity found here, can be used as an alternative technique.
Keywords: turkey coronavirus; poult enteritis and mortality syndrome; immunohistochemistry